Welcoming Africa's children : Theological and ministry perspectives - Breed, Gert; Grobbelaar, Jan; Grobbelaar, Jan (Durbanville AOSIS, 2016)
The purpose of this book is to combine perspectives of scholars from Africa on Child Theology from a variety of theological sub-disciplines to provide some theological and ministerial perspectives on this topic. The book disseminates original research and new developments in this study field, especially as relevant to the African context. In the process it addresses also the global need to hear voices from Africa in this academic field. It aims to convey the importance of considering Africa$1 (Bs children in theologising. The different chapters represent diverse methodologies, but the central and common focus is to approach the subject from the viewpoint of Africa$1 (Bs children. The individual authors$1 (Bvaried theological sub-disciplinary dispositions contribute to the unique and distinct character of the book. Almost all chapters are theoretical orientated with less empirical but more qualitative research, although some of the chapters refer to empirical research that the authors have performed in the past. Most of the academic literature in the field of Child Theologies is from American or British-European origin. The African context is fairly absent in this discourse, although it is the youngest continent and presents unique and relevant challenges. This book was written by theological scholars from Africa, focussing on Africa$1 (Bs children. It addresses not only theoretical challenges in this field but also provides theological perspectives for ministry with children and for important social change. Written from a variety of theological sub-disciplines, the book is aimed at scholars across theological sub-disciplines, especially those theological scholars interested in the intersections between theology, childhood studies and African cultural or social themes. It addresses themes and provides insights that are also relevant for specialist leaders and professionals in this field. No part of the book was plagiarised from another publication or published elsewhere.s
North-West University
English
Keywords: Christian theology; africa; child theology; practical theology; african socio-cultural; childhood studies; Bible; Christian ministry; God; Hermeneutics; Holism; Jesus; South Africa